1992
DOI: 10.1073/pnas.89.10.4588
|View full text |Cite
|
Sign up to set email alerts
|

Gamma delta T-cell receptor repertoire in acute multiple sclerosis lesions.

Abstract: ABSTRACTyS T cells are a distinct lymphocyte population that can exhibit reactivity with heat shock proteins over- RESULTSAccumulation of y6T Cells in Acute MS Plques. a4and y8 T-cell populations were examined in frozen tissue specimens from five postmortem cases with MS, one case with subacute sclerosing panencephalitis (SSPE), and five cases without neurological disease. Frozen sections were stained with hematoxylin/eosin, oil red-O (ORO), and mAbs specific for CD2 and the interleukin 2 receptor. Both the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
155
0
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(166 citation statements)
references
References 13 publications
10
155
0
1
Order By: Relevance
“…Thus, the two subsets use different adhesion molecules and signaling pathways to transmigrate, suggesting that resident and circulating ␥␦ T lymphocytes are equipped with distinct biochemical and molecular mechanisms to regulate their selective tissue localization. This might also account for the finding that in relapsing-remitting MS, ␥␦ T cells found in the lesions differ from those in CSF (5,6,12,31), supporting the hypothesis that the two ␥␦ T cell subsets play distinct roles in the pathogenesis of the disease.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Thus, the two subsets use different adhesion molecules and signaling pathways to transmigrate, suggesting that resident and circulating ␥␦ T lymphocytes are equipped with distinct biochemical and molecular mechanisms to regulate their selective tissue localization. This might also account for the finding that in relapsing-remitting MS, ␥␦ T cells found in the lesions differ from those in CSF (5,6,12,31), supporting the hypothesis that the two ␥␦ T cell subsets play distinct roles in the pathogenesis of the disease.…”
Section: Discussionsupporting
confidence: 51%
“…Several cell types and soluble mediators contribute to the onset and progression of demyelinization, including T lymphocytes (2-4); in particular, some previous reports point to an active role played by the ␥␦ T cell subset in the pathogenesis of MS (5)(6)(7).…”
Section: T Is Well Accepted That Multiple Sclerosis (Ms)mentioning
confidence: 99%
“…The description of such repeated sequences in the PBL of healthy donors is unprecedented since only a few V81-J81 sequences have been published to date (28)(29)(30)(31). Two studies showed an unrestricted repertoire in PBL from patients and normal controls, but predominant sequences in acute multiple sclerosis (29) and leprosy lesions (28), respectively, suggesting in situ selection of particular VIS1 + cells by so far undefined antigens. One further study demonstrated a restricted V/~I repertoire in the peripheral blood of certain patients with rheumatoid arthritis but not in four healthy controls (30).…”
Section: Discussionmentioning
confidence: 99%
“…In the present work, we have shown that V81-J81junctions, while displaying the extensive alterations of germline sequences that are characteristic of post fetal stages (14), are not randomly represented among PBL V/$1 + cells in a large fraction of healthy donors. The description of such repeated sequences in the PBL of healthy donors is unprecedented since only a few V81-J81 sequences have been published to date (28)(29)(30)(31). Two studies showed an unrestricted repertoire in PBL from patients and normal controls, but predominant sequences in acute multiple sclerosis (29) and leprosy lesions (28), respectively, suggesting in situ selection of particular VIS1 + cells by so far undefined antigens.…”
Section: Discussionmentioning
confidence: 99%
“…wide range of physiological functions, they may also be involved in autoimmunity (5)(6)(7). A striking example of a putatively autoimmune human ␥␦-TCR 2 was described in 1991 (8).…”
mentioning
confidence: 99%